Cryotherapy is preferable to ablative CO2 laser for the treatment of isolated actinic keratoses of the face and scalp: a randomized clinical trial. (1st May 2014) - Zane, C.; Facchinetti, E.; Rossi, M.T.; Specchia, C.; Ortel, B.; Calzavara‐Pinton, P.
Summary: Background: Actinic keratosis (AK) may progress to squamous cell carcinoma. In the case of normal or mildly photodamaged skin, lesion‐directed treatments are considered valuable options despite poor published evidence of their therapeutic activity. Objectives: The aim of this single‐centre, open‐label, prospective, nonsponsored, randomized, controlled clinical trial was to compare CO2 laser ablation with cryotherapy in the treatment of isolated AKs of the face and scalp. Patients and methods: Patients with isolated (≤ 4) AKs of the face and scalp were randomized to receive CO2 laser ablation or cryotherapy. After 90 days, the overall complete remission (CR) rates of patients and lesions were assessed and correlated with thickness grade. Results: Two hundred patients with a total number of 543 AKs were enrolled. The CR rates of lesions after 3 months were 78·2% with cryotherapy and 72·4% with CO2 laser ablation. Thicker lesions were significantly more responsive to cryotherapy ( P = 0·034). Seventy‐three patients (71·6%) had CR of all lesions 3 months after cryotherapy and 64 (65·3%) after laser ablation. At 12 months after treatment the number of patients with CR was reduced to 53 with cryotherapy and 14 with laser ablation. Conclusions: The rate of patients and lesions with CR is similar after 3 months, but more patients remain in stable remission for 12 months after cryotherapy. Cryotherapy is more effective for thick lesions. The cosmetic outcome was good or excellent in almost all patients.